Susceptibility of clinical isolates of Staphylococcus aureus strains to 32 antibiotics - H. O. K Tanzil; R. Warsa (Indonesian Pediatric Society, 1973)
Previous studies in this department on the activity of various antibioticsagainst clinical isolates showed that Staphylococcus aureus strains were the most frequent microorganisms encountered in clinical specimens (Tan et al., 1968; Tanzil et al., 1971; Tanzi! and Warsa, 1971, 1972).